Oncogenic Network and Hub Genes for Natural Killer/T-Cell Lymphoma Utilizing WGCNA - Liu, Huijiao; Liu, Mei; You, Hua; Li, Xiru; Li, Xiangdong (Frontiers in Oncology, 2020)
Natural killer (NK) /T cell lymphoma (NKTCL) is a subtype of non-Hodgkin lymphoma with aggressive progression and poor prognosis, the molecular mechanisms of NKTCL have not been well studied. Herein, we revealed the lymphoma associated dysregulated genes and signaling pathways or biological processes in NKTCL. We characterized that the ECM receptor interaction pathway and T cell receptor signaling pathway were the main dysregulated pathways in NKTCL by Gene Ontology (GO) analysis and pathway enrichment analysis. By using weight gene co-expression network analysis (WGCNA), gene co-expression network of NKTCL (SRP049695) was constructed and hub genes (LMO3, GRB14) were identified. In addition, another GEO dataset (GSE69406) was used to validate these hub genes. Furthermore, these hub genes were identified and validated by survival analysis (GSE90597). These results provided novel insights into the pathogenesis of NKTCL. Of particular, LMO3 and GRB14 might as potential oncoproteins and biomarkers for the diagnosis and treatment of NKTCL.